Discovery of Drug Candidates for Specific Human Disease Based on Natural Products of Gut Microbes - Wang, Cheng-Yu; Wen, Qing-Feng; Wang, Qiao-Qiao; Kuang, Xia; Dong, Chuan; Deng, Zi-Xin; Guo, Feng-Biao (Frontiers in Microbiology, 2022)
The beneficial metabolites of the microbiome could be used as a pool for screening drugs that have potential for therapy of various human diseases. Narrowing down the ran 1ge of beneficial metabolite candidates in specific disease was a primarily key step for next further validations in model organisms. Herein, we proposed a reasonable hypothesis that the metabolites existing commonly in multiple beneficial (or negatively associated) bacteria might have a high probability being effective drug candidates for specific disease. According to this hypothesis, we screened metabolites associated with seven human diseases. For type I diabetes, 45 out of 88 screened metabolites had been reported as potential drugs in the literature. Meanwhile, 18 out of these metabolites were specific to type I diabetes. Additionally, metabolite correlation could reflect disease relationship in some sense. Our results have demonstrated the potential of bioinformatics mining gut microbes’ metabolites as drug candidates based on reported numerous microbe-disease association and VMH database. More subtle method would be developed to ensure more accurate predictions.